Immunity in acute myeloid leukemia: Where the immune response and targeted therapy meet. Issue 1 (1st November 2021) - Fink, Avner; Hung, Eric; Singh, Indranil; Ben‐Neriah, Yinon
Abstract: Acute myeloid leukemia (AML) is a highly aggressive disease with high relapse and mortality rates. Recent years have shown a surge in novel therapeutic development for AML, both in clinical and preclinical stages. These developments include targeted therapies based on AML‐specific molecular signatures as well as more general immune modulation and vaccination studies. In this review, we will explore the evolving arena of AML therapy and suggest some intriguing connections between immune system modulation and targeted therapy. Improved understanding of the immune system involvement in various stages of the disease and the crosstalk between immune effectors, targeted therapy, and AML cells can provide a better framework for designing the next generation of AML therapies. Abstract : The past few years have witnessed a remarkable progress in targeted therapy of acute myeloid leukemia (AML). In parallel, there is an accumulating evidence for immune regulation and emerging modalities of immunotherapy in AML. Here, we describe the cross‐impact of targeted and immunotherapy in AML.